Media ensembles and educational self-perception: A study of Peruvian users - Mateus, Julio-César (2024)
This study explores the media practices of Peruvian internet users based on their self-perceived educational level. The purpose is to provide an original theoretical perspective on the formation of media assemblages, shaped by the uses and interactions of specific social groups with media outlets. Utilizing a custom questionnaire, grounded in an updated version of the Uses and Gratifications Theory, administered to a sample (n=465) of users from various age groups and socioeconomic backgrounds, we examine the similarities and differences in these media assemblages and their impact on users' agency as critical media consumers. The results reveal that the national context, characterized by technological disparities and the COVID-19 pandemic, has influenced consumption practices. The smartphone stands out as the most widely used device, valued for its immediacy and diverse content. Both less educated and highly educated groups resort to it for information, education, and entertainment. Television also plays a significant role, serving as entertainment for older generations and a source of information for higher socioeconomic levels. The choice of streaming services among different income groups reflects the influence of connectivity and bandwidth. Information consumption is driven by curiosity, while entertainment is used for learning and following trends. Furthermore, there is little planning involved in entertainment and information consumption, although educational content is more planned among the highly educated group. This difference may be linked to access opportunities for educational materials, suggesting avenues for future research.